La pérdida de las raíces sociales de la acción política juvenil - Anleo Sánchez, Juan María González (Miscelánea Comillas, 2011)
The current economic crisis in Spain has shown very clearly, more than ever, the apathy of the Spanish population in general and the youth in particular when confronting the responsible political and economic decision makers. In this context, however, many youth experts are drawing the attention to the fact that the involvement of youth policy, far from being diminished, is being transferred to forms of political action more informal and flexible. The data collected from the last report of the Spanish Youth Foundation SM 2010, however, sufficiently indicates not only that this transfer is not occurring but also that the political apathy of modern Spanish youth is deeply rooted in social disaffection.